Educational directions for the teacher: Theoretical approach - Aimeur, Sihem (Journal of Human Sciences, 2023)
The goal of every teacher in the different stages of education is to fulfill his pedagogical tasks and achieve the goals of the educational process. Therefore, we have dealt with some pedagogical orientations that allow to know the foundations, skills and tasks of effective teaching, in addition to the principles of the management of educational situations and how to deal with the difficulties of classroom management. In order to achieve these objectives, certain principles must be taken into account in course planning, including the following: - Know the different characteristics of learners in terms of grade level, problems, abilities, needs and interests. - Master the subject of study and have a good knowledge of the content of the curricula. - Know the different pedagogical strategies, and thus lay out the bases of the pedagogical methods adapted to the nature of the subject, the targeted skill, the level of the learners and the means available.